Frazeologizmy w przekładzie na język kaszubski baśni Jana Drzeżdżona - Makurat, Hanna (Slavia Occidentalis, 2017)
The article discusses the methods used to translate phrasemes in the Kashubian version of the book Baśnie. Brawãdë by Jan Drzeżdżon. The translator, Roman Drzeżdżon, was unable to find any equivalent phrasemes in the target language. He translated them literally or described their meaning. Moreover, he also used the compensation strategy and introduced phrasemes in places where they were absent in the original.